Differential equations to calculate the ionicity factor of hexagonal structure semiconductors - Ghassan E., Arif; Yarub, Al-Douri, Assoc. Prof. Dr.; Farah Aini, Abdullah, Dr.; Rabah, Khenata, Prof. Dr. (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/